2019
DOI: 10.1111/febs.15082
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity to DNA double‐strand breaks associated with PARG deficiency is suppressed by exo‐1 and polq‐1 mutations in Caenorhabditis elegans

Abstract: Deficiency of either of the two homologs of poly(ADP‐ribose) glycohydrolase (PARG), PARG‐1 and PARG‐2, in Caenorhabditis elegans leads to hypersensitivity to ionizing radiation (IR). In the germ cells of parg‐2 mutant worms, the dissipation of recombinase RAD‐51 foci was slower than in wild‐type (WT) cells, suggesting defects in DNA double‐strand break (DSB) repair via homologous recombination (HR). Nevertheless, RPA‐1, the large subunit of replication protein A, accumulated faster in parg‐2 worms and disappea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
0
9
1
Order By: Relevance
“…PARG-1 is the main PAR glycohydrolase in the germ line. The C. elegans genome encodes two orthologs of mammalian PARG, PARG-1, and PARG-2 7,8,41 . Both mutants are hypersensitive to IR exposure and more recently it was shown that parg-2 is involved in the regulation of HR-dependent repair of ectopic DSBs by influencing the extent of resection upon IR 41 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PARG-1 is the main PAR glycohydrolase in the germ line. The C. elegans genome encodes two orthologs of mammalian PARG, PARG-1, and PARG-2 7,8,41 . Both mutants are hypersensitive to IR exposure and more recently it was shown that parg-2 is involved in the regulation of HR-dependent repair of ectopic DSBs by influencing the extent of resection upon IR 41 .…”
Section: Resultsmentioning
confidence: 99%
“…The C. elegans genome encodes two orthologs of mammalian PARG, PARG-1, and PARG-2 7,8,41 . Both mutants are hypersensitive to IR exposure and more recently it was shown that parg-2 is involved in the regulation of HR-dependent repair of ectopic DSBs by influencing the extent of resection upon IR 41 . To explore possible functional links or redundancies between parg-1 and parg-2, we used CRISPR to engineer parg-2 null mutations in both the wild type (WT) and parg-1(gk120) deletion mutant backgrounds (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is also posited, that once PARylation caused the recruitment of XRCC1, removal of the PAR chain facilitates the translocation of XRCC1 from PAR directly to the DNA strand break and increases the repair kinetics of downstream processes [72]. In contrast to humans, worms have two functional orthologues of the glycohydrolase [73,74]. Evaluation of basal PAR levels of these two PARG deletion mutant strains, parg-1(∆) and parg-2(∆), showed significant differences between the glycohydrolase activities (Figure 8A).…”
Section: Reverse Genetic Studies Indicate a Slight Phenotype Of The Nth-1(∆) Mutant And Significant Differences In Parg-1 And Parg-2 Actimentioning
confidence: 99%
“…C. elegans genome encodes two PARGs: pme-3 and pme-4, which share 18% and 22% overall identity, and 42% and 40% PARG motif similarity to human PARG, respectively (St-Laurent et al, 2007). Knockdown (RNAi) of both genes results in enhanced sensitivity to ionizing radiation (St-Laurent et al, 2007), which can be suppressed by an impaired TLS pathway via mutational deactivation of POLQ (Bae et al, 2020). Despite the presence of these enzymes in C. elegans, there is no direct evidence to link the PARPs and PARGs to the BER pathway.…”
Section: Poly(adp-ribose)polymerasesmentioning
confidence: 99%